2022
DOI: 10.2147/idr.s356606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Time to Recovery of Admitted COVID-19 Cases at Dilla University Referral Hospital Treatment Center, South Ethiopia

Abstract: Background Since coronavirus disease 2019 emergence, millions were infected and many were dying because of the virus. Clinical features and time to recovery of admitted clients vary across settings. Therefore showing clinical features and recovery time from COVID-19 in a different setting is necessary to design appropriate treatment and preventive measures. So, this study attempted to investigate the clinical features and time to recovery of admitted clients to Dilla University Referral Hospital t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(37 reference statements)
1
5
2
Order By: Relevance
“…In this study majority of patients were male (62.6%) this finding was in line within most literatures elsewhere in Pakistan (70.25 %) [11] Wuhan from China (53.8%) [12] Northern Ethiopia (63.3%) [17], (south Ethiopia (55.9%) [20] (Addis Ababa (71%) [26] Ethiopia treatment center (69.5%) [23]. This finding suggested that the prevalence of COVID-19 infections was highest among males.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study majority of patients were male (62.6%) this finding was in line within most literatures elsewhere in Pakistan (70.25 %) [11] Wuhan from China (53.8%) [12] Northern Ethiopia (63.3%) [17], (south Ethiopia (55.9%) [20] (Addis Ababa (71%) [26] Ethiopia treatment center (69.5%) [23]. This finding suggested that the prevalence of COVID-19 infections was highest among males.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding death and sex in our study, 62.6% of dead patients were male, this is higher than the study conducted in Brazil [15] (55.4%) Dilla University [20] (57.1%), but also lower than (71%) study conducted in Ethiopia [26].…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations